High-Entropy Perovskite Oxide: A New Opportunity for Developing Highly Active and Durable Air Electrode for Reversible Protonic Ceramic Electrochemical Cells - Zuoqing Liu; Zhengjie Tang; Yufei Song; Guangming Yang; Wanru Qian; Meiting Yang; Yinlong Zhu; Ran Ran; Wei Wang; Wei Zhou; Zongping Shao (Nano-Micro Letters, 2022)
Abstract Reversible proton ceramic electrochemical cell (R-PCEC) is regarded as the most promising energy conversion device, which can realize efficient mutual conversion of electrical and chemical energy and to solve the problem of large-scale energy storage. However, the development of robust electrodes with high catalytic activity is the main bottleneck for the commercialization of R-PCECs. Here, a novel type of high-entropy perovskite oxide consisting of six equimolar metals in the A-site, Pr1/6La1/6Nd1/6Ba1/6Sr1/6Ca1/6CoO3−δ (PLNBSCC), is reported as a high-performance bifunctional air electrode for R-PCEC. By harnessing the unique functionalities of multiple elements, high-entropy perovskite oxide can be anticipated to accelerate reaction rates in both fuel cell and electrolysis modes. Especially, an R-PCEC utilizing the PLNBSCC air electrode achieves exceptional electrochemical performances, demonstrating a peak power density of 1.21 W cm−2 for the fuel cell, while simultaneously obtaining an astonishing current density of − 1.95 A cm−2 at an electrolysis voltage of 1.3 V and a temperature of 600 °C. The significantly enhanced electrochemical performance and durability of the PLNBSCC air electrode is attributed mainly to the high electrons/ions conductivity, fast hydration reactivity and high configurational entropy. This research explores to a new avenue to develop optimally active and stable air electrodes for R-PCECs.